GIS tourism web based at Kampung Seberang Ramai, Perlis / Muhammad Safwan Najmi Shaari - Shaari, Muhammad Safwan Najmi (2022)
Tourism is an industry that has a significant economic impact because it contributes to the development of other industries through a multiplier effect. Geographical Information System (GIS) technology has a lot of potential applications in tourism management and planning. Some of the significant aspects of GIS that might assist tourist planning are managing spatial data and giving essential value-added information. The location of Kampung Seberang Ramai, which is relatively unknown to the general public, makes this area challenging to discover when using a hardcopy map. So, to solve this issue, it is necessary to create a web-based version of this area for public users to access and visualize. This study aims to encourage Kampung Seberang Ramai to become an attractive tourism sector in Perlis. The objectives of this study are i) to collect the tourism information and places using geospatial approach, ii) to develop an interactive tourism web-based at Kampung Seberang Ramai, and iii) to test the output of GIS tourism web-based system. The website was developed using the waterfall model. This web-based generated using open sources like Wix Web Editor. In system testing, analysis can be made of the web-based development by distributing the questionnaire to 30 respondents and analyzing user satisfaction on the GIS tourism web-based development. This study has benefited tourists in obtaining information about tourism in Perlis. The result for this study is a product of web-based GIS on Kampung Seberang Ramai, Perlis, and one of the ways to help the development of tourism in the country.